A Comparative Study of Cobalt Chalcogenides as the Electrode Materials on Lithium‐Sulfur Battery Performance. Issue 2 (16th December 2021) - Wang, Xuejie; Zhu, Bicheng; Liu, Tao; Zhang, Liuyang; Yu, Jiaguo
Abstract: Lithium‐sulfur batteries, as viable options for energy storage, have gained popularity because of their high energy density. However, the poor conductivity of sulfur and Li2 S, as well as the shuttling effect of lithium polysulfides, seriously limits their commercialization. Herein, cobalt chalcogenides (Co3 O4, CoS, and Co3 Se4 ) supported by reduced graphene oxide are synthesized as the electrode materials, which feature high conductivity, rapid kinetic conversion, and catalytic effect. Based on complementary experimental outputs and advanced computation, it is revealed that the change in anion results in distinctive performance. Among them, the cathode material based on Co3 Se4 /reduced graphene oxide is the best. The reasons can be ascribed to the conductive and catalytic improvement. This comparative study provides guidelines in the design of lithium‐sulfur batteries via the meticulous regulation of the anions. Abstract : Cobalt chalcogenides supported by reduced graphene oxide (rGO) are designed to study their effect on a lithium‐sulfur battery. Comprehensively, Co3 Se4 /rGO, featured with optimal band structure and bond length, is proved to be the ideal host due to the balance between adsorption of polysulfides and catalytic effect.